Association of Geographic location and Dental Caries - A Retrospective Study - PRATHA, A. ASHWATHA; BALASUBRAMANIAM, ARTHI; JAIN, RAVINDRA KUMAR (The journal of contemporary issues in business and government, 2021)
Dental caries is one of the most common global health problems today. Geographic variation in terms of culture and ethnicity plays an important role in oral health practices, which in turn contributes to major oral health diseases such as dental caries and periodontitis.This study was aimed to find the association between geographic location and dental caries.This retrospective study was conducted using records of patients visited private Dental College. A total of 150 consecutive case records of patient age ranging from 15-90 years were retrieved. Data on the number of “D” component of Decayed, Missing and Filled teeth Index from their records were entered and subjected to statistical analysis. Descriptive statistics was done to present the proportion of decayed teeth. Chi-square association was performed to find the association. A minimum of one to five decayed teeth was present in 32.67% of rural patients and 50% of urban patients. Seven to ten decayed teeth was more prevalent (16%) in rural patients and less prevalent (0.67%) in urban patients. A maximum of eleven to fifteen decayed teeth was seen only in rural patients. A statistical significant association was found between geographic location and dental caries (p=0.000). This necessitates to provide oral health awareness on food habits among people in the rural population.